Pelatihan Pembuatan Bubuk Kaldu Jamur Sebagai Pengganti Msg Bagi Jama’ah Majelis Taklim Nurul Iman - Sufinatin Aisida; Adibah Adibah (Lembaga Pengembangan Kinerja Dosen, 2025)
The Nurul Iman taklim council congregation has a desire to fill other activities besides daily routines with useful activities if possible to increase family income. Seeing the impact of MSG which has become a reasonable partner, there are other alternatives as flavoring, the abundance of oyster mushrooms on the market and a stable price are raised in this service activity. The goal is none other than to provide new science and skills about the natural flavoring of oyster mushrooms. The service method is carried out by FGD, socialization, demonstration and evaluation. Based on the results of the mentoring activity, a survey poll was obtained with 6 questions for the assisted partners, after the completion of this activity, 18 assisted partners expressed their agreement with the satisfaction of this service activity, the remaining 3 people answered yes